2015
DOI: 10.2308/iace-51261
|View full text |Cite
|
Sign up to set email alerts
|

Using Rubrics to Assess Accounting Learning Goal Achievement

Abstract: This paper illustrates the development and use of rubrics to improve the learning assessment process and enhance the teaching-learning relationship. We highlight the multidimensional benefits of rubrics as valuable tools for student assessment (grading), course assessment (at the instructor level), and program assessment (at the administrator/curriculum committee/accreditation level). Moreover, rubrics may improve qualitative feedback on learning to students and instructors. Development of effective rubrics is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…MCQs were also found to have a positive impact on performance in examinations. Schaefer and Stevens (2016) advocate the use of rubrics in promoting student learning. They highlight the benefits of using rubrics in, among others, course assessment.…”
Section: Other Assessment Methodsmentioning
confidence: 99%
“…MCQs were also found to have a positive impact on performance in examinations. Schaefer and Stevens (2016) advocate the use of rubrics in promoting student learning. They highlight the benefits of using rubrics in, among others, course assessment.…”
Section: Other Assessment Methodsmentioning
confidence: 99%
“…Our review of student papers and reflections is based on a rubric, Appendix B, that corresponds to the learning objectives listed in the Introduction. Rubrics enhance learning and reduce bias and subjectivity by providing "a systematic approach to measuring learning outcomes" (Schaefer and Stevens 2016). The rubric contains a criterion related to ethical challenges faced by the business world in general (accounting-related careers), plus a criterion related to any ethical challenges faced by the interviewee.…”
Section: Assessment Rubricmentioning
confidence: 99%
“…The researcher [5] points out that a very important component for entering the accounting profession has been created in many educational institutions around the world, which is considered to be an academic discipline. The authors [6] have suggested that rubrics that can be applied can be useful and valuable to achieve the expected results. They managed to introduce some important elements such as the measurement of accounting content, the methodology of scientific research in the field of accounting as well as critical thinking.…”
mentioning
confidence: 99%